Francesca Rosenberg on her experience as Director of Community, Access, and School Programs at the Museum of Modern Art (New York) - Torres, Sara; Rosenberg, Francesca (Arte, Individuo y Sociedad, 2017)
Francesca Rosenberg is the Director of Community, Access, and School Programs. She has played a key role in the inception of programs working with people living with dementia and their care partners at MoMA. Part of her activity includes the launch of the Meet Me program and The MoMA Alzheimer’s Project: Making Art Accessible to People with Dementia.